The glory of the age is the wisdom of grey hair: association of physician appearance with outcomes in hospitalised medical patients – an observational study (Swiss Medical Weekly, 2019)
INTRODUCTION The physical appearance of a physician may influence patients’ perceptions of that physician’s quality of care. There is a lack of studies investigating whether physician appearance is indeed associated with patient satisfaction and mortality. METHODS This observational study included adult medical inpatients treated at a Swiss tertiary care hospital between 2013 and 2016. We investigated associations of gender and physician appearance (hair colour, wearing of glasses) with in-hospital mortality and perceived quality of care, assessed by a telephone interview 30 days after admission. Regression models were adjusted for patient age, patient gender, and the Charlson Comorbidity Index. RESULTS We included 18,259 inpatients treated by 494 different physicians during their hospital stay. We had full information regarding patient-perceived quality of care for 9917 patients. Overall, 860 patients (4.7%) died in the hospital and 1479 (14.9%) reported low satisfaction with their care. After multivariable adjustment, there was no difference in mortality or patient-perceived quality of care whether physicians did or did not wear glasses and whether they were male or female. The hair colour of residents was also not associated with outcomes. However, patients treated by grey-haired attending physicians, compared to those with dark or blond hair, had significantly lower in-hospital mortality (adjusted odds ratio 0.70, 95% confidence interval 0.53–0.92, p = 0.011). CONCLUSIONS This analysis suggests that physician gender or appearance has little influence on the quality of care provided to hospitalised medical patients. Whether the small but significant mortality benefit observed for grey-haired attending physicians is possibly confounded by age and physician experience clearly needs further investigation. Nevertheless, our analysis provides empirical evidence that having at least some grey-haired attending physicians in the medical physician team seems to be beneficial for patients, even if patients do not recognise the clear superiority of their care.